Characteristics of Motor Dysfunction in Longstanding Human Immunodeficiency Virus. (7th October 2019) - Robinson-Papp, Jessica; Gensler, Gary; Navis, Allison; Sherman, Seth; Ellis, Ronald J; Gelman, Benjamin B; Kolson, Dennis L; Letendre, Scott L; Singer, Elyse J; Valdes-Sueiras, Miguel; Morgello, Susan
Abstract: Background: Cognitive dysfunction in human immunodeficiency virus (HIV) has decreased, but milder forms of HIV-associated neurocognitive disorders (HAND) persist along with motor dysfunction. The HIV Motor Scale (HMS) is a validated tool that captures motor abnormalities on routine neurologic examination and which is associated with cognitive impairment in HIV. In this study, we applied a modified HMS (MHMS) to a nationwide cohort of people with longstanding HIV to characterize and understand the factors contributing to motor dysfunction. Methods: The National NeuroAIDS Tissue Consortium is a nationwide longitudinal cohort study. Participants undergo regular assessments including neurological examination, neuropsychological testing, and immunovirologic data collection. Data from examinations were used to calculate the MHMS score, which was then correlated with history of AIDS-related central nervous system (CNS) disorders (ARCD; eg, prior CNS opportunistic infection), cerebrovascular disease (CVD), and HAND. Results: Sixty-nine percent of participants showed an abnormality on the MHMS, with 27% classified as severe. Results did not vary based on demographic or immunologic variables. The most common abnormalities seen were gait (54%), followed by coordination (39%) and strength (25%), and these commonly co-occurred. CVD ( P = .02), history of ARCD ( P = .001), and HAND ( P = .001) were all associated with higher (ie, worse) HMS in univariate analyses; CVD and ARCD persisted in multivariate analyses. CVD was also marginally associated with symptomatic HAND. Conclusions: Complex motor dysfunction remains common in HIV and is associated with CVD, ARCD, and to a lesser extent, HAND. Future studies are needed to understand the longitudinal trajectory of HIV-associated motor dysfunction, its neural substrates, and impact on quality of life. Abstract : Motor dysfunction, especially gait impairment, is common in longstanding human immunodeficiency virus (HIV); it is associated with cerebrovascular disease, a prior history of an AIDS-related central nervous system disorder, and to a lesser extent, a diagnosis of HIV-associated neurocognitive disorder.